Postpartum Depression and Its Impact on Maternal Infant Bonding and Early Breastfeeding Practices - Khan, Muhammad Muslim; Fatima, Fatima; Naila, Naila; Jamal, Izaz; Gul, Ijaz; Muneeb, Pirzada (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum depression (PPD) is certainly called a mental health disorder that occurs after the birthing process, and is a disorder that hands down one of the most harmful factors relating to the childbirth process, infant health, and mortality. Disregarding the psychological aspects of the mothers, PPD has the potential to damage the bonding process between the mother and infant, and create an unhealthy mother–infant relationship. PPD also affects the initial breastfeeding of the infant, and breastfeeding is one of the most important aspects of the baby’s health. PPD also influences the psychological and emotional development of the infant. Objectives: Determining the rate of postpartum depression in postnatal women and its relationship with the mother–infant bond and the initiation and exclusivity of early breastfeeding. Methodology: This cross-sectional study targeted women who postnatal attend a follow-up clinical appointment within the first six weeks after delivery. Depression during the postpartum period was measured utilizing the Edinburgh Postnatal Depression Scale. Maternal infant bonding was measured through a tested bonding questionnaire. Breastfeeding practices were also measured through interviews regarding the time of initiation and exclusivity. The SPSS software version 24.0 was used to analyze the data, and a p-value of less than 0.05 was deemed to be statistically significant. Results: A total of 150 postnatal women were included, with a mean age of 27.6 ± 4.8 years. Postpartum depression was identified in 46 participants (30.7%). Mothers with PPD demonstrated significantly lower maternal–infant bonding scores compared to non-depressed mothers (42.3 ± 6.1 vs. 51.7 ± 5.4; p < 0.001). Early initiation of breastfeeding within one hour of birth was significantly lower among depressed mothers (54.3% vs. 78.1%; p = 0.002). Exclusive breastfeeding rates were also significantly reduced in women with postpartum depression (p = 0.004). Conclusion: Postpartum depression is quite common, which is correlated with difficulties with bonds between the sufferers and their children and problems with breastfeeding. Psychosocial interventions adapted to the digital format could help improve the mental health and outcomes for the children of affected mothers.